Interest rate dynamics and monetary policy implementation in Switzerland - Puriya Abbassi; Dieter Nautz; Christian J. Offermanns (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2009)
The maturity of the operational target of monetary policy is a distinguishing feature of the SNB's operational framework of monetary policy. While most central banks use targets for the overnight rate to signal the policy-intended interest rate level, the SNB announces a target range for the three-month Libor. This paper investigates the working and the consequences of the SNB's unique operational framework for the behavior of Swiss money market rates before and during the financial crisis.
Keywords: E52; E58; 330; Implementation of Monetary Policy; Operational Targets of Monetary Policy; Three-Month Rate Targeting; Financial Crisis.; Zins; Geldmarkt; Finanzmarktkrise; Zinspolitik; Geldpolitisches Ziel; Schweiz